Corporate voluntary disclosure via WeChat - Li, Ying; Huang, Qianqian; Yuan, Tao (Journal of Banking & Finance, 2025)
This paper examines how Chinese firms use WeChat for voluntary disclosure. Using a topic model, we classify over 1.6 million WeChat articles into two categories: “relevant” and “noise” articles. We find that on days when firms publish value-relevant articles, there is a significant increase in abnormal returns and stock liquidity. Further analyses reveal that WeChat serves as an alternative disclosure channel for providing new information. Firms also use WeChat to complement mandatory disclosure. However, we find that firms with negative earnings tend to issue more noise articles around earnings announcements. These noise articles are associated with higher short-term announcement returns in cases of significantly negative earnings events. These results suggest that firms may engage in opportunistic WeChat disclosure behavior. Collectively, our study highlights the significant role of WeChat in the voluntary disclosure practices of Chinese companies.